PENGARUH BULLYING TERHADAP KECERDASAN INTERPERSONAL SISWA DI SD PELANGI KOTA KUPANG - Adoe, Treesly Y.N; Tasekeb , Ruthilda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study discusses the effect of Bullying on Students’ Interpersonal Intelligence.  This study is motivated by the phenomenon of bullying that occurs in the school environment which causes students who are victims of violence from bullying actions to find it difficult to build communication and socialize with the surrounding environment or in other words they have difficulty developing their interpersonal intelligence or social intelligence.The purpose of this study is to examine the effect of bullying on interpersonal intelligence. The type of research used is quantitative research. The research method uses descriptive method. The instrument used is a questionnaire. The sampling technique in this study is to use non probability sampling technique purposive sampling type, the sample used is grade 4-6. This research was conducted at Sd Pelangi Kupang Jl. Bogenville No.3 Tabun, Alak District, Kupang city. Based on the research, it was found that all indicators of bullying and interpersonal intelligence obtained the results of hypothesis test calculations using simple linear regression tests with the calculation tool is SPSS 21 version 21, the results were seen from Sig. (2-tailed) < ɑ 0.05 which is 0.03 this indicates that H₀ is rejected and Hɑ is accepted.  This means that there is a significant influence between bullying on interpersonal intelligence.